Drug utilization pattern during pregnancy in Nekemte referral hospital: a cross sectional study - Asfaw, Fanaye; Bekele, Mekdes; Temam, Shemsiya; Kelel, Musin (International Journal of Scientific Reports, 2016)
Background: Pregnancy is a period of great physiological changes to the mother and fetus in which every malfunction of the body as the result of drug use may lead to serious consequences in both. It is a period that demands special care to the health care service providers. Therefore, the objective of this project is to conduct across sectional study on drug utilization pattern during pregnancy in Nekemte referral hospital, Ethiopia from 2012-2013 that could lay base for the maternal care programs. Methods: A purposive sampling was used to draw 100 pregnant women from the source population. Data were collected from the documented drug administration record of Nekemte referral hospital for all stages of pregnancy, types of drugs, roots of administration and dosage forms for all the pregnant female who were admitted to the hospital. Results: Among the pregnant women, who visited Nekemte referral hospital during the study period, the majority (96%) had a record for drug (s) and almost similar pattern of records were found in all wards for drug use. Of all the pregnant women, there was a high record for drug utilization of the women in the first trimester. Unemployed and uneducated pregnant females make the highest proportion. There was also a prescription of potentially dangerous drugs during pregnancy in Nekemte referral hospital. Conclusions: Many pregnant women were found using drugs during pregnancy in Nekemte referral hospital, including potentially harmful drugs. Therefore, there should be intensive assessment of pregnant women treatment in line with the US food and drug administration agency (FDA) risk category and locally operating regulations by considering risks and benefits to both mothers and the foetus in drug prescription and administration.